Aplikasi Bursa Kerja Khusus Berbasis Delphi 7 Menggunakan Barcode (Studi Kasus di SMK Negeri 2 Karanganyar) - Muklis; Cicilia Puji Rahayu; Taman Ginting (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2019)
The phases of making a special job market application for SMK Negeri 2 Karanganyar based on Delphi 7 with barcode began with designing and creating a database using Microsoft Access 2007. The database created is a student database, login database, database card, databease registration, database selection, company database, database permission search and database. Next to design and make the program using Delphi 7. In this application program there is a login form, main form, registration form, selection form, search form, company form, student database form, user form manager and permission form. The next stage is designing the registration report, selection report, permit report, registration card report and the last trial and implementation program. This program is implemented in the special job market of SMK Negeri 2 Karanganyar and according to the results of respondents' assessment that this program is very helpful for special job market officials to be more efficient in data collection and processing, and to help smooth officers in the input and management of registrant data.